A bibliometric analysis of acupuncture for cerebral infarction from 1993 to 2023 - Zhao, Yanqing; Huang, Li; Li, Wentao; Cai, Li (Frontiers in Neurology, 2024)
Objective: This research aims to probe the inclination and mapping knowledge domain of acupuncture for cerebral infarction through bibliometrics. Methods: Retrieve publications related to acupuncture for cerebral infarction from the Web of Science core collection database from 1993 to December 31, 2023. Subsequently, a domain knowledge graph was constructed using VOSviewer, CiteSpace, GraphPad Prism, and Scimago Graphica. Results: The cumulative publication trend is increasing year by year. China is the most productive country. Close cooperation between countries is mainly distributed in Europe. Institutional cooperation is mostly limited to Chinese universities of traditional Chinese medicine. Tao Jing is the most productive author, "Stroke" journal has the most publications, and the most important journal is Acupuncture Electro Therapeutics Research. Zhang SH is the most cited author, Si QM is a hot author in this field, rehabilitation treatment after cerebral infarction is a high-frequency research, and nerve regeneration is a hot keyword in this field. Long EZ's 1989 paper published in the journal Stroke is an important reference. The hot papers are Donnan GA (2008) and Wu P (2010), "population-based study", "Baihui Acupoint", "memory deficits", "neurotrophic factor" and "randomized trial" which are the main study contents in the field.Through the bibliometric analysis of the study on acupuncture for cerebral infarction in the Web of Science database, this review further delineates a knowledge map of countries, authors, institutions, cited authors, keywords, cited references in the field of acupuncture for cerebral infarction, which has a momentous guiding significance for quickly and accurately positioning the key information in the field.